Evaluation of diabetes knowledge of pharmacy students - TEZCAN, SONGÜL; RABUŞ, ŞULE (My University, 2023)
Diabetes is a global health concern. Pharmacists contribute to improving health outcomes by providing pharmaceutical care to patients with Diabetes Mellitus (DM). There are studies showing that pharmacy students need more knowledge in order to competently contribute to diabetes management. The aim of this study is to determine the level of diabetes knowledge of the undergraduate students of Health Sciences University Hamidiye Faculty of Pharmacy. A cross sectional study using online self-administered survey was conducted during 2 weeks among the 4th and 5th year pharmacy students. Sociodemographic characteristics of the students were collected. A structured questionnaire about the definition, causes and symptoms of diabetes (40 items) [1] were applied. The response options were “yes; no; or I do not know”. Each correct answer was scored as 1 point, incorrect or I don't know answers are scores as 0 point. The maximum possible score was 40. Diabetes Knowledge Scale scores and the correlation of the scores with students’ sociodemographic characteristics are main outcome measures. Of the 196 students 77% were female and 43.4% of them had diabetes family history. Forty-one percent of the participants stated that they were involved in the care of at least one diabetes patient. The mean knowledge score was found to be as 34.07 ± 4.13. The subscale scores were found to be as follows; diabetes general knowledge 7.04 ± 1.15 (8 items), diabetes risk factor 2.88 ± 0.37 (3 items), diabetes symptoms 2.70 ± 0.53 (3 items), diabetes diagnosis 3.46 ± 0.91 (4 items), diabetes treatment 7.64 ± 1.62 (10 items), diabetes complications 3.81 ± 0.58 (4 items), and diabetes diet and exercise 3.78 ± 1.19 (5 items), and diabetes control 2.76 ± 0.48 (3 items). The Cronbach's alpha value of the scale was found to be 0.767. Students were found to have adequate background knowledge regarding diabetes diagnosis, symptoms, and risk factors. However, knowledge deficits in areas such as diet in diabetes and treatment in gestational diabetes have been identified among participants.